Determining the possibility of placing turbine systems for hydraulic regulation and production of electrical energy in the District Heating Network in Krakow - Natkaniec Piotr (EDP Sciences, 2021)
This article presents the methods of specifying the potentiality of energy recovery in the turbine installations projected to hydraulic regulation of the heating medium in the Krakow District Heating System. To achieve this, creating hydraulic calculations enabling to indicate the best places to install turbines in District Heating System is necessary. For this reason, a great amount of work - like choosing a methodology and optimal calculation program, creating an actual database for calculations - has to be done. Hydraulic calculations will also help to determine optimal parameters of future instalments, select the most suitable devices necessary for the proper working of turbine installations and create the future impact assessment to District Heating System.